The World of Jules Robinet: Pioneer Winemaker - Cecillon, Jack (Ontario History)

(untitled) (The Ontario Historical Society, 2018)
In the 1880s, the southwestern region of Ontario, including Essex County and Pelee Island, became home to a series of pioneering winemakers. While the story of the winemakers of Pelee Island has been told, far less has been written about the vineyards of the Windsor border region. Jules Robinet, emerged as a successful winemaker at the turn of the 20th century after a series of hardships wiped out most of his competition. In time, Robinet`s business flourished with the enactment of Prohibition laws in Canada and the United States. An immigrant from Rougemont, France, Robinet served as a key link in the migration chain of French labourers and grape growers who settled in and around the Town of Sandwich. For French immigrants, he emerged as an employer, business associate, and advocate for the community that found its roots in the very same region of France.